1994
DOI: 10.1111/j.1432-1033.1994.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Monoxide Stretching Modes in Camphor‐Bound Cytochrome P‐450cam

Abstract: The effect of pH, monovalent cations, glycerol, temperature, and pressure on the carbonmonoxy (CO) stretching mode of camphor-bound cytochrome P-450,-(CYP 101) was studied. Two effects, band overlap and frequency shift, have been observed. The CO stretch infrared band located at about 1940 cm-I is asymmetric because of the overlap of three bands at about 1931 cm-I, 1939 cm-I, and 1942 cm-' with strongly different populations. Reducing the temperature or increasing the pressure leads to splitting the band or sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…For these studies, the Soret band [151, 152] and the stretching mode vibration of CO bound to the reduced enzyme (monitored by IR spectroscopy) are utilized as spectral probes [153]. Also, flash photolysis [154, 155] and stopped-flow [150, 156] techniques have been employed under high pressure in order to investigate the steps involved in binding of substrates.…”
Section: High Pressure Spectroscopymentioning
confidence: 99%
“…For these studies, the Soret band [151, 152] and the stretching mode vibration of CO bound to the reduced enzyme (monitored by IR spectroscopy) are utilized as spectral probes [153]. Also, flash photolysis [154, 155] and stopped-flow [150, 156] techniques have been employed under high pressure in order to investigate the steps involved in binding of substrates.…”
Section: High Pressure Spectroscopymentioning
confidence: 99%
“…An indirect method is a water replacement technique using a probe molecule. In a large number of studies [4–9] using different approaches we found that the CO iron ligand is a good probe for the polarity and therefore for the presence of water molecules in the heme environment of cytochrome P450cam.…”
mentioning
confidence: 99%
“…The spectra obtained in this way correspond to an absorbance difference spectrum between the absolute spectrum of the CO bound form in the dark (so-called dark-spectrum) and the absolute spectrum of the photolyzed sample (so-called light-spectrum). For the darkspectrum of (1R)-camphor-bound P-450 we have shown elsewhere [12] that the infrared band is asymmetric which results from an overlap of the subconformer bands. Similar behavior is observed also for (1S)-camphor-bound P-450¢~m CO, however, with different shape (Schulze, H., private communication).…”
Section: Introductionmentioning
confidence: 99%